Split intein-mediated selection of cells containing two plasmids using a single antibiotic - Palanisamy, Navaneethan; Degen, Anna; Morath, Anna (Nature Communications, 2019)
Engineering cell lines often requires multiple plasmids with different selection markers. Here the authors present SiMPl, a method based on rationally engineered split enzymes which get reconstituted via intein-mediated protein splicing to maintain two plasmids using a single antibiotic.
Gesehen am 04.12.2019